Health-related quality of life during early aggressive treatment in patients with polyarticular juvenile idiopathic arthritis: results from randomized controlled trial - Maarit Tarkiainen; Pirjo Tynjälä; Paula Vähäsalo; Liisa Kröger; Kristiina Aalto; Pekka Lahdenne (BMC, 2019)
Abstract Background Juvenile Idiopathic Arthritis (JIA) may cause significant impairment in health-related quality of life (HrQoL), despite effective therapies. The aim of this study was to assess HrQoL during first-year treatment in patients with new-onset polyarticular JIA, and to compare treatment strategies. Methods In ACUTE-JIA Study, 60 patients with new-onset JIA were randomized to receive either infliximab with methotrexate (IFX+MTX); a triple therapy of methotrexate, hydroxychloroquine, and sulfasalazine (Triple); or methotrexate monotherapy (MTX). Efficacy was measured with American College of Rheumatology pediatric (ACRp) score, and juvenile arthritis disease activity score (JADAS). HrQoL was evaluated with Child Health Questionnaire (CHQ), which includes physical and psychosocial summary scores (PhS and PsS). Linear mixed models were utilized to compare groups over time. Results In the whole group of 60 patients, mean physical summary score (PhS) improved from 26.2 (SD 8.7) at week 0 to 49.7 (SD 13.2) at week 54 (p=0.046). Mean improvement of PhS was 20.3 (95% CI -15.5 to 56.2); 22.6 (-19.5 to 64.7); and 26.6 (-12.1 to 65.3) in IFX+MTX, Triple, and MTX, respectively. Changes in psychosocial summary score (PsS) were smaller: from 51.0 (SD 8.5) to 54.7 (6.3) (p=0.019) in all patients. No differences between the three treatment groups were detected in either of the measures. In multivariate analyses, Child Health Assessment Questionnaire (CHAQ), pain VAS, and time spent in inactive disease contributed to improvement in PhS; gender and CHAQ to PsS. Conclusions HrQol improved during the first year on therapy for JIA irrespective of the treatment strategy. The timing of change in the different dimensions of HrQoL varied; improvement occurred earlier in physical than psychosocial domains of HrQol. Trial registration This study was registered within the Hospital District of Helsinki and Uusimaa (http://www.hus.fi) clinical trials, number 211864 in October 2002, and later on with ClinicalTrials.gov, number NCT01015547.